2010
DOI: 10.1089/vbz.2009.0182
|View full text |Cite
|
Sign up to set email alerts
|

The First Report ofHepatozoon canisIdentified inVulpes vulpesand Ticks from Italy

Abstract: This is the first report on the presence of Hepatozoon canis in Vulpes vulpes in Italy. During the years 2005 and 2006, a total of 119 foxes were collected and their spleen tissues were screened by microscopy, polymerase chain reaction, and sequencing. In the same area, 290 ticks were picked off from dogs or collected from the environment. Microscopy detected inclusion bodies regarded as belonging to the genus Hepatozoon in four samples, whereas molecular diagnostics evidenced 16 foxes (13.4%) and 6 ticks (2.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 30 publications
3
40
0
1
Order By: Relevance
“…Most infections have been identified by examination of blood smears and were classified as H. canis, a cosmopolitan parasite of canids; however, recent genetic characterization has revealed that numerous variants, subspecies, or cryptic species of H. canis exist worldwide (East et al 2008;Gabrielli et al 2010;Starkey et al 2013). In wild canids, Hepatozoon infections are typically subclinical (McCully et al 1975), but a non-H. canis species of Hepatozoon was reported to cause clinical disease in spotted hyenas in Tanzania (East et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Most infections have been identified by examination of blood smears and were classified as H. canis, a cosmopolitan parasite of canids; however, recent genetic characterization has revealed that numerous variants, subspecies, or cryptic species of H. canis exist worldwide (East et al 2008;Gabrielli et al 2010;Starkey et al 2013). In wild canids, Hepatozoon infections are typically subclinical (McCully et al 1975), but a non-H. canis species of Hepatozoon was reported to cause clinical disease in spotted hyenas in Tanzania (East et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, this association was not found in rural dogs in the state of Rio de Janeiro (O'DWYER et al, 2001). Other tick species have been identified as possible hosts, such as Haemaphysalis flava in Japan (MURATA et al, 1995) and Ixodes ricinus in Italy (GABRIELLI et al, 2010).…”
Section: Transmissionmentioning
confidence: 99%
“…Hepatozoon spp. have been detected in canid species that occur in Africa such as golden jackals C. aureus (Duscher et al 2013), black-backed jackals Canis mesomelas (McCully et al 1975), African wild dogs Lycaon pictus (Williams et al 2013), and red foxes Vulpes vulpes (Gabrielli et al 2010).…”
Section: Introductionmentioning
confidence: 99%